SELECTED FACTORS IN THE LOCATION OF SERVICE ACTIVITIES CONDUCTED BY SMALL ENTERPRISES - Chrobocińska, Katarzyna (Management and Administration Journal, 2020)
AbstractThe optimal location of a company is an asset in the market game, it is particularly important in activities where direct contact with the customer is essential. A well-used location of an entity increases the chance of achieving future profits, it is an important source of competitive advantage in service activities such as tourism, gastronomy or cosmetics. This study aimed to assess the most important factors that affect the location of small service enterprises operating in the Warmińsko-Mazurskie Voivodship. The survey was conducted by the standardised interview method with a survey questionnaire and an in-depth interview. The research findings have shown that the ranking of location factors changes due to their importance for the development of business activity. The optimal location of small service companies offering services in a traditional and/or mixed manner was determined by the following factors: Internet access, the potential for the company spatial expansion, the costs of maintaining the premises, the number of future customers and customers’ demographic characteristics, the closeness of competitors, the cost of building purchase/rental, local taxes and fees and availability of parking space.